2017
DOI: 10.1038/s41598-017-01478-w
|View full text |Cite
|
Sign up to set email alerts
|

Teosinte in Europe – Searching for the Origin of a Novel Weed

Abstract: A novel weed has recently emerged, causing serious agronomic damage in one of the most important maize-growing regions of Western Europe, the Northern Provinces of Spain. The weed has morphological similarities to a wild relative of maize and has generally been referred to as teosinte. However, the identity, origin or genetic composition of ‘Spanish teosinte’ was unknown. Here, we present a genome-wide analysis of single-nucleotide polymorphism (SNP) data for Spanish teosinte, sympatric populations of cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 35 publications
1
54
0
2
Order By: Relevance
“…Vertical gene transfer from maize is limited to Zea species. Wild relatives of maize outside cultivation are not known/reported in Europe (Eastham and Sweet, ; OECD, ; EFSA, ; Trtikova et al., ). Therefore, potential vertical gene transfer is restricted to maize and weedy Zea species, such as teosintes, and/or maize‐teosinte hybrids, occurring in cultivated areas (EFSA, ; Trtikova et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…Vertical gene transfer from maize is limited to Zea species. Wild relatives of maize outside cultivation are not known/reported in Europe (Eastham and Sweet, ; OECD, ; EFSA, ; Trtikova et al., ). Therefore, potential vertical gene transfer is restricted to maize and weedy Zea species, such as teosintes, and/or maize‐teosinte hybrids, occurring in cultivated areas (EFSA, ; Trtikova et al., ).…”
Section: Assessmentmentioning
confidence: 99%
“…If spread, establishment and hybridisation are per se considered acceptable in agro-environments, they do not exceed the LoC and no risk management measures are required. This has recently been the case with the reporting of maize–teosinte hybrids in European agro-ecosystems [48–50]. Due to the GM trait conferring herbicide tolerance, the occurrence of GM maize × teosinte hybrids was considered to be restricted to agricultural fields and therefore, the potential harm considered manageable [51].…”
Section: Resultsmentioning
confidence: 99%
“…Other crop plants such as maize do not outcross, spread or persist without human intervention in a particular environment and can be removed once the cultivation has been terminated. Recently, experiments indicated that hybridization of cultivated maize with a weedy relative, the teosinte, can occur [50] and may, therefore, also spread and persist in the environment. It is most difficult to retrieve populations of feral crop plants such as GM oilseed rape from the environment, because (i) oilseed rape can build up long persisting soil seed banks and establish stable and self-dispersing feral populations [53, 54] and (ii) there is evidence that feral oilseed rape populations disperse beyond the arable land [55, 56].…”
Section: Resultsmentioning
confidence: 99%
“…mexicana, the genetic analysis conducted by Vilaplana and Díaz (un‐published data) and published by Trtikova et al . () revealed that the analysed populations do not group with any of the currently recognised teosinte taxa. These authors suggest that the weed might be of admixed origin, most likely involving Zea mays ssp.…”
Section: Introductionmentioning
confidence: 86%